Correlation Between Emotional Intelligence and Critical Thinking Skills of Elementary School Students - Anggun Safitri; Gupo Matvayodha; Muhaiminah Jalal (al-Afkar, Journal For Islamic Studies, 2026)
Critical thinking skills are essential competencies that elementary school students need to possess in order to face the challenges of the 21st century. One factor that is presumed to be related to these skills is emotional intelligence. This study aimed to determine the relationship between emotional intelligence and the critical thinking skills of fifth-grade students at SDN 131/IV Jambi City. The research employed a quantitative approach with a correlational design. The study involved 35 fifth-grade students from class V-B selected through purposive sampling. Data were collected using emotional intelligence and critical thinking skills questionnaires that had met validity and reliability requirements. Data were analyzed using the Pearson Product-Moment Correlation test with the assistance of SPSS software. The results revealed a positive and significant relationship between emotional intelligence and students’ critical thinking skills, with a correlation coefficient of 0.831 and a significance value of 0.000 (p < 0.05). These findings indicate that higher emotional intelligence is associated with better critical thinking skills. Therefore, the development of emotional intelligence should receive greater attention in elementary school learning processes.